Calendar festive and ritual culture of the Mordva-Moksha of Bashkiria (traditions in the realities of modernity) - Ranus R. Sadikov (Финно-угорский мир)
Introduction. Calendar rituals represent a key element of the ethnic traditions of any people. Despite the extensive scholarly exploration of traditional Mordovian rituals, their manifestations within diaspora communities – particularly among the Moksha residing in the territory of Bashkiria – remain insufficiently studied. Through prolonged interaction with Turkic peoples, the Moksha have preserved many ethno-differentiating features of their culture. The aim of the study is to analyze the current state of the calendar festive and ritual culture of the Mordvin-Moksha population in Bashkiria.